't Knalpotteke ; Knalpot (Antwerpen: Atthis)
"Fonds Suzan Daniel (FSD)Vanaf 01(1979-80) 5: KnalpotPeriodiciteit : tweemaandelijksRedactie : Burgemeester Woutersstraat 5, 2600 Berchem ; vanaf 01(1979-1980) 7 : Verbondstraat 53, 2000 Antwerpen ; vanaf 14(1991-1992) 1 : Volksstraat 7, 2000 Antwerpen ; vanaf 19(1996-1997) 4 : Geuzenstraat 27, 2000 Antwerpen"